The effects of mergers: an international comparison; Die Effekte von Fusionen: Ein internationaler Vergleich - Klaus Gugler; Dennis C. Mueller; B. Burcin Yurtoglu; Christine Zulehner (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
This paper analyzes the effects of mergers around the world over the past 15 years. We utilize a large panel of data on mergers to test several hypotheses about mergers. The effects of the mergers are examined by comparing the performance of the merging firms with control groups of nonmerging firms. The comparisons are made on profitability and sales. The results show that mergers on average do result in significant increases in profits, but reduce the sales of the merging firms. Interestingly, these post merger patterns look similar across countries. We also did not find dramatic differences between mergers in the manufacturing and the service sectors, and between domestic and cross-border mergers. Conglomerate mergers decrease sales more than horizontal mergers. By separating mergers into those that increase profits and those that reduce them and by then examining the patterns of sales changes following the mergers, we determine the effects of mergers on efficiency and market power. Our results suggest that those mergers that decrease profits and efficiency account for a large proportion. However, we can also identify mergers that increase profits by either increasing market power or by increasing efficiency. The first conclusion seems to be a more likely explanation for large companies, whereas the latter is likely to be true for small firms. – – Dieser Artikel analysiert die Effekte von Fusionen, die weltweit über die letzten 15 Jahre stattgefunden haben. Wir vergleichen die Gewinn- und Umsatzentwicklung von fusionierenden Firmen mit der Entwicklung von nicht-fusionierenden Firmen. Die Resultate zeigen, dass Fusionen im Durchschnitt zu signifikant höheren Profiten führen, aber dass die Umsätze im Vergleich zur Kontrollgruppe zurückbleiben. Interessanterweise sind diese Effekte bei Vergleichen zwischen den verschiedenen Ländern, bei einem Vergleich zwischen Industriesektor und Dienstleistungssektor bzw. zwischen nationalen und grenzüberschreitenden Fusionen ziemlich ähnlich. Konglomerate Fusionen reduzieren die Umsätze mehr als horizontale Fusionen. Um die Effekte der Fusionen auf die Marktmacht bzw. die Effizienz zu analysieren, teilen wir zuerst die Fusionen in gewinnsteigernde und gewinnreduzierende Fusionen, um dann die Umsatzentwicklung zu betrachten. Unsere Resultate zeigen, dass ein großer Prozentsatz der Fusionen die Gewinne und die Effizienz reduzieren. Wir können jedoch auch Fusionen identifizieren, die die Gewinne entweder durch Marktmacht- oder Effizienzsteigerungen erhöhen. Die erste Erklärung ist wahrscheinlicher für große Firmen, die zweite für kleine Firmen.
Keywords: G34; L2; 330; Mergers; Acquisitions; International Comparison